Comparative assessment of prognostic value for revised-mayo risk model and child-pugh score in patients with primary sclerosing cholangitis - Öztaş, Erkin; Özer Etik, Diğdem; Metin, Rahşan Olga; Kalkan, İsmail Hakkı and Parlak, Erkan and Önder, Fatih Oğuz and Arhan, Mehmet and Şaşmaz, Nurgül (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: The aim of this study was to compare the utility of the revised Mayo risk model (rMRM) and Child-Pugh scores (CPSs) for predicting the prognosis of disease in patients with primary sclerosing cholangitis (PSC). Materials and Methods: Patients were divided into 2 groups: Group I (37 patients; alive and not requiring liver transplantation) and Group II (8 patients; deceased or requiring liver transplantation). rMRM suggests the possible survival percentage over a 4-year period. Thus, rMRM scores and CPSs on the first visit were calculated from the data at the time of diagnosis for patients diagnosed with PSC <4 years ago. rMRM scores and CPSs of patients with >4 years of follow-up were calculated using data from the visit 4 years prior to their last follow-up. Results: Bivariate analyses showed that need for liver transplantation/mortality was correlated with either first visit CPS (r=0.481, p=0.001) or rMRM (r=0.452, p=0.002). Analysis of the area under the curve showed that both models performed similarly in terms of predicting the need for liver transplantation/mortality (rMRM: 0.780; CPS: 0.762; p=0.8). There was a significant difference in Kaplan-Meier survival rates between Group I and Group II for both risk models (rMRM: p<0.001; CPS: p<0.001) when the decisive event was death or need for liver transplantation. Conclusion: Both rMRM and CPSs are useful in risk assessment of patients with PSC. The ability to predict prognosis is similar for both risk models.